Comparison of high flow oxygen therapy in children with respiratory distress due to bronchiolitis and pneumonia - Surabhi, Uday S.; Basavaraja, Gangasamudra Veerappa; Ahmed, Maaz; Tummala, Sujith Kumar (International Journal of Contemporary Pediatrics, 2021)
Background: Respiratory support through high flow nasal cannula (HFNC) therapy has emerged as a new method to provide respiratory support with bronchiolitis. Aim was to study outcome of HFNC therapy in children with bronchiolitis and pneumonia. Methods: The study was a prospective observational study involving children admitted to pediatric intensive care unit with respiratory distress (RD) in the age group of 1 month to 6 years over a period of 3 months (February 2017 till April 2017). Severity was assessed by clinical respiratory score (CRS). Children with RD were initiated with high flow nasal cannula. During treatment various parameters including CRS were documented at baseline and at 15 min and then hourly in a carefully designed performa. The primary outcome was failure of HFNC and need for ventilation. Results: Sixty children were included in the study of which 22 (37%) were in the bronchiolitis group and 38 (63%) were in the pneumonia group. 38 children presented with severe RD and 19 children with moderate RD. There was significant decrease in heart rate (HR) (20%), respiratory rate (RR) (20%) and in CRS within 1 hour of HFNC with a clinical stabilization within 24 hours in 16 cases (27%), 24-48 hours in 35 cases (58%) and >48 hours in 5 (8%) cases. Therapy was successful in 55 (92%), and failed in 5 (8%). Conclusions: HFNC has better outcome in children with RD due to acute bronchiolitis when compared to pneumonia. HFNC can be safely commenced in RD in critically ill child with monitoring.